Organizational climate and teachers' job satisfaction in residential and non residential schools - Ong, Boon Puah (1997)
The usefulness of teacher perceptual data in school organizational climate and job satisfaction research was illustrated by a study of two selected residential and two non residential schools in Kuala Lumpur. Seven school climate dimensions of mission and goal consensus, empowerment, student support, affiliation, professional interest, resource adequacy and work pressure were assessed by seventy teachers from residential schools and sixty four teachers from non residential schools. Comparisons of school climate in the selected residential and non residential schools revealed statistically significant difference on six dimensions, namely mission and goal consensus, empowerment, student support, affiliation, professional interest and resource adequacy. Teachers in the selected residential schools perceived more positive school environments than teachers in the selected non residential schools. The selected school teachers' job satisfaction were determined by two separate measures of facet specific and facet free job satisfaction. Comparisons of teachers' facet specific job satisfaction in residential and non residential schools revealed no statistically significant difference on teachers' intrinsic, extrinsic and social satisfaction. Nevertheless, comparisons of teachers' facet free job satisfaction in residential and non residential schools revealed statistically significant difference on all the five global measures of occupation satisfaction, occupation expectation satisfaction, present job satisfaction, re-entry and optional retirement decision. Teachers in residential schools were found to be more satisfied with their facet free overall job satisfaction. Analysis for the combined sample revealed that majority of the teachers were satisfied with their social satisfaction; only three out of ten teachers perceived high level of intrinsic satisfaction while seven out of ten teachers were dissatisfied with extrinsic satisfaction. The overall job satisfaction for the combined sample was only at the medium level. This study also revealed that majority of the combined sample only perceived highly of affiliation while the perceptions for empowerment, student support, professional interest, mission and goal consensus, resource adequacy and work pressure dimensions were only at the medium level.